Modulation of gene expression in MHCC97 cells by interferon alpha - Wu, Wei-Zhong (World J Gastroenterol, 2005)
AIM: To elucidate the molecular mechanisms of the inhibitory effects of IFN-α on tumor growth and metastasis in MHCC97 xenografts. METHODS: Three thousand international units per milliliter of IFN-α-treated and -untreated MHCC97 cells were enrolled for gene expression analysis using cDNA microarray. The mRNA levels of several differentially expressed genes in cDNA microarray were further identified by Northern blot and RT-PCR. RESULTS: A total of 190 differentially expressed genes including 151 IFN-α-repressed and 39 -stimulated genes or expressed sequence tags from 8 464 known human genes were found to be regulated by IFN-α in MHCC97. With a few exceptions, mRNA levels of the selected genes in RT-PCR and Northern blot were in good agreement with those in cDNA microarray. CONCLUSION: IFN-α might exert its complicated anti-tumor effects on MHCC97 xenografts by regulating the expression of functional genes involved in cell metabolism, proliferation, morphogenesis, angiogenesis, and signaling.